Compression after impact strength of composite sandwich panels - Davies, G.A.O.; Hitchings, D.; Besant, T.; Clarke, A.; Morgan, C.
Two types of sandwich panels with carbon epoxy skins and aluminium honeycomb core were subjected to low velocity impacts and then the damaged panels tested for their compression-after-impact (CAI)strength. One type of panel was found to be a very robust energy absorber, i.e. a thick-skin thin-core option. The other panels with their thin skins and thick core were found to penetrate easily whereupon the impactor forced the back-face to debond massively. These panels then had the worst CAI strength. Both the impact damage and the CAI behaviour--to failure--were simulated using a finite element model of skins and core. The model gave very respectable agreements with the impact tests even though the damage in skin and core were extremely complex mechanisms, involving progressive fibre fracture in the skin and elasto-plastic deformation in compression and shear in the honeycomb core. The model for CAI strength predicted well the failure load and the mode of propagation from the damaged zone. 2003 Elsevier Ltd. All rights reserved.
Keywords: IMPACT DAMAGE; CAI STRENGTH; SANDWICH PANELS; FE MODEL PREDICTION